Teachers’ Perspectives on Integrating Information Technology into Biology Education Management in Senior High Schools - Manggopa, Hiskia Kamang; Kumampung, Deislie R. Henrieta; Batmetan, Johan Reimon (JR Education, 2025)
This study explores biology teachers’ perspectives on integrating information technology (IT) into biology education management in senior high schools. A qualitative phenomenological approach was employed to capture teachers’ lived experiences in using IT for curriculum planning, instructional delivery, assessment, and administrative tasks. Data were collected through in-depth semi-structured interviews with 12 senior high school biology teachers selected via purposive sampling. Observations and document analyses were also conducted to triangulate the findings. Teachers perceive IT integration as enhancing instructional efficiency, increasing student engagement, and supporting better data management. However, challenges such as inadequate infrastructure, limited technical skills, and inconsistent institutional support hinder optimal implementation. Teachers adopt adaptive strategies, including peer mentoring, blended learning models, and leveraging freely available online tools. School leaders should strengthen technical infrastructure, provide continuous professional development, and establish supportive policies for IT-based biology education management. This study provides a nuanced understanding of teachers’ real-world experiences in managing biology education with IT, offering context-specific insights for developing targeted policies and training programs.